Tranexamic acid for spontaneous intracerebral hemorrhage: a randomized controlled pilot trial (ISRCTN50867461) - Sprigg, Nikola; Renton, Cheryl J.; Dineen, Robert A.; Kwong, Yune; Bath, Philip M.W. (Elsevier, 2014)
Background: Spontaneous intracerebral hemorrhage (ICH) can be devastating, particularly if hematoma expansion (HE) occurs. Tranexamic acid (TA), an antifibrinolytic drug, significantly reduced mortality in bleeding patients after trauma in the large CRASH-2 trial. The CRASH-2 ICH substudy found that TA nonsignificantly reduced mortality and dependency in traumatic ICH. The aim of this study was to assess the feasibility of performing a randomized controlled trial of tranexamic acid in spontaneous ICH, ahead of a definitive study. Methods: We performed a single-center, prospective, randomized (2:1), double-blind, placebo-controlled blinded endpoint trial of TA (intravenous 1 g bolus, 1 g infusion/8 h) in acute (<24 hours) spontaneous ICH. The primary objective was to test the feasibility of recruiting to the trial. Other objectives included tolerability (adverse events) and the effect of TA on HE and death and dependency. Results: The trial was feasible, with 24 patients enrolled (TA, n 5 16; placebo, n 5 8) between March 2011 and March 2012, and acceptable—only 3 patients declined to participate. All patients received the correct randomized treatment; 1 patient in the TA group did not complete the infusion because of neurologic deterioration. There were no significant differences in secondary outcomes including adverse events, HE, death, and dependency. One patient in the TA group had a deep vein thrombosis. Conclusions: This, the first randomized controlled trial of TAin ICH, found that the protocol could be delivered on schedule (2 patients/mo) and was feasible. Larger studies are needed to assess safety and efficacy of TA in ICH.